2008
DOI: 10.1177/1753944708090170
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Local TAT-p27Kip1 Fusion protein inhibits cell proliferation in rat Carotid arteries

Abstract: Taken together, these results provide evidence that TAT-p27(Kip1) can inhibit vascular cells proliferation. It is the first successful demonstration that the cell permeable TAT-p27(Kip1) has potential as a vascular anti-proliferative agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Extracellular p27 decreased proliferation of examined cell lines, depending on the type of cells and form of p27 protein. Similar results were observed earlier on variety of tumor cell lines [31] as well as on rabbit endothelial cells [32].…”
Section: Discussionsupporting
confidence: 90%
“…Extracellular p27 decreased proliferation of examined cell lines, depending on the type of cells and form of p27 protein. Similar results were observed earlier on variety of tumor cell lines [31] as well as on rabbit endothelial cells [32].…”
Section: Discussionsupporting
confidence: 90%
“…Although a complete molecular mechanism for this wide range of defects is currently unknown, our findings suggest a defect in the p27 Kip1 pathway, and the remodeling of the primitive coronary plexus, possibly related to compact myocardial thinning. Finally, the findings reported here represent the basis for new insight into the development of cardiac malformations in general.p27 Kip1 is up‐regulated in 14‐3‐3ε −/− (Kosaka et al, ) and can play a crucial role at several levels because of its ubiquitous expression (Neukamm et al, ; Sakai et al, ; Merchant et al, ). In this study, we identified abnormal patterning of p27 Kip1 in the myocardial wall as well as the endocardial and possibly the epicardial populations.…”
Section: Discussionmentioning
confidence: 73%
“…The latter has been described in the Ptx1 mutant mouse (Bergwerff et al, 1998), which, however, cannot yet be conclusively linked to the findings in 14-3-3e À/À hearts or p27 Kip1 expression. Nevertheless, all differentiated cellular contributions to the arterial pole vasculature express 14-3-3e (McConnell et al, 1995) and p27 Kip1 (Neukamm et al, 2008;Sakai et al, 2010). Remodeling of the aortic (pharyngeal) arch arteries is known to be related to NCC and the second heart field (Bartram et al, 2001;Molin et al, 2002;Molin et al, 2003;Poelmann et al, 2004;Ward et al, 2005;High and Epstein, 2008;Keyte and Hutson, 2012), as well as Notch (High and Epstein, 2008) and TGFb signaling (Bartram et al, 2001;Molin et al, 2002;Molin et al, 2003).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasssalo et al. unpublished data) and during adventitia remodelling in rat carotid artery injury (Neukamm et al. 2008).…”
Section: Discussionmentioning
confidence: 99%